Western blotting of NC1 type IV collagen fragments in human plasma - Werle, Egon; Hao, Lansheng; Hasslacher, Christoph; Fiehn, Walter (European journal of clinical investigation, 1997)
Collagen IV matrix of glomerular basement membrane may be involved in the development of various renal diseases, e.g. diabetic nephropathy. An immunoblotting method for the detection of the carboxy-terminal non-collagenous (NC1) domain of type IV collagen in plasma was developed. The high sensitivity down to the picogram range enabled characterization of NC1(IV) fragments in human blood for the first time. Both Western blotting and gel filtration chromatography coupled with an enzyme-linked immunoassay surprisingly revealed that the NC1(IV)-related components are bound to the fibrin clot forming during blood coagulation. About 40% of the NC1(IV) fragments in plasma had an apparent molecular mass higher than 340 000. Abnormal NC1(IV) immunoblot patterns were observed in about 50% of patients with insulin-dependent (n = 20) and non-insulin-dependent (n = 20) diabetes mellitus compared with less than 7% in healthy control subjects (n = 30). There were no obvious associations between abnormal immunoblots and stage of nephropathy or glycaemic control in diabetic subjects.